Standardizing Central Line Safety: Lessons Learned for Physician Leaders. (May 2014) - Mueller, Jeff T.; Wright, Alan J.; Fedraw, Leslie A.; Murad, M. Hassan; Brown, Daniel R.; Thompson, Kristine M.; Flick, Randall; Seville, Maria Teresa A.; Huskins, W. Charles
A comprehensive central venous catheter (CVC) safety program reduces mechanical and infectious complications and requires an integrated multidisciplinary effort. A multistate health care system implemented a discovery and diffusion project addressing CVC insertion, maintenance, and removal. Process and outcome measures were collected before and after the intervention. The project was completed in 12 months. It was associated with statistically significant improvement in 6 process measures and reduction in the rate of ICU central line-associated bloodstream infection (from 1.16 to 0.80 infections/1000 catheter days; incidence rate ratio = 0.69; 95% confidence interval = 0.51, 0.93). A comprehensive CVC standardization project increased compliance with several established best practices, was associated with improved outcomes, produced a refined definition of discovery and diffusion project components, and identified several discrete leadership principles that can be applied to future clinical improvement initiatives.